PERANCANGAN JARINGAN RT/RW NET BERBASIS TEKNOLOGI FIBER TO THE HOME (FTTH) DI DUSUN KEDON RT.005 BANTUL - Noraga, Bima; Suharjo, Imam (JATISI, 2025)
The planning of the Fiber to the Home (FTTH) network development in Dusun Kedon Rt.005 Bantul focuses on enhancing fast and stable internet access for the community. In today's digital era, the need for reliable internet connectivity is increasingly important, especially in rural areas that are often neglected in terms of information technology infrastructure. The RT/RW Net network in Dusun Kedon is designed using the FTTH method, utilizing Mikrotik RB750r2 devices, Optical Line Terminal (OLT), Optical Distribution Cabinet (ODC), Optical Distribution Point (ODP), and Optical Network Terminal (ONT). A comparison between the use of FTTH networks and point-to-point networks shows several advantages and disadvantages, including. (1) In the FTTH network, the optical fiber from the provider is split using a splitter to serve multiple customers, while in point-to-point, the optical fiber is directly connected from the service provider to the customer's location. (2) The performance of the FTTH network is influenced by the number of users since the bandwidth is shared, whereas point-to-point offers more stable performance without bandwidth sharing. (3) The FTTH network requires fewer cables and hardware components compared to point-to-point. (4) The FTTH network is more vulnerable to failure if the splitter or main fiber experiences damage, which can affect multiple users simultaneously. In contrast, a point-to-point failure only affects a single customer. (5) The implementation and maintenance costs of the FTTH network are lower compared to point-to-point.